Ficus septica Burm. F. Leaves Ethanolic Extract Induces Apoptosis in 7,12-Dimethylbenz[A]Nthracene-Induced Rat Liver Cancer Quatitavely - Dita Brenna Septhea; Anindyajati Anindyajati; Andita Pra Darma; Ika Nurzijah; Agung Endro Nugroho; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2011)
The chemopreventive effect of Ficus septica Burm. f. leaves ethanolic extract (FLEE) was studied in 7,12-dimethylbenz[a]nthracene(DMBA)-induced rat liver cancer. Rats were divided into 5 group, 5 rats (5 wk of age Sprague Dawley rat) in each group. Group 1 was control diet group, administered with 0,5% CMC-Na as vehicle. FLEE was administered 750 mg/kgBW and 1500 mg/kgBW starting 4 wk until 5 wk after DMBA administration at the first until fifth wk to group 2 and group 3. Group 4 was control extract group, administered with 750 mg/kgBW and group 5 was DMBA group. DMBA is a carcinogen to induce liver cancer was also administered in DMBA control group and all animals were necropsied at 6 wk after DMBA administration. Activity of inducing apoptosis was detected using Double Staining method in 750 mg/kgBW FLEE group compared to control group but no in 1500 mg/kgBW FLEE group resulted in 100% dead. Apoptotic cells would have orange flourescence but normal cells would have green flourescence detected by flourescence microscope. To investigate the protein that involved in apoptotic mechanism, we studied p53 expression using Imunohistochemistry (IHC). There was no difference expression of p53 in both tested and control groups. Based on the results, FLEE has a potency as chemoprentive agent because its activity on inducing apoptosis in liver cancer with p53-independent pathway. The mechanism of apoptosis induction of this extract needs to be explored by observing the expression of related proteins.Keywords: apoptosis, Ficus septica, liver cancer, p53 independent pathway